2008
DOI: 10.1111/j.1365-2184.2008.00549.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of pRb by cyclin D kinase is necessary for development of cardiac hypertrophy

Abstract: These results indicate that cyclin D-cdk4/6-dependent phosphorylation of pRb and activation of E2F is necessary for hypertrophic growth in cardiomyocytes, whereas cyclin E-cdk2 kinase is not necessary for hypertrophy but regulates endoreplication in these cells. The data support the notion that hypertrophic growth of cardiomyocytes involves a partial progression through the G1 phase of the cell cycle

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…The accumulation of pRb plays a critical role in regulating cell cycle arrest associated with terminal cardiac muscle differentiation, as also observed in other in vitro culture systems, including skeletal muscle, adipocytes, and macrophages, suggesting that this may be a general phenomenon (5,15,16). However, other mechanisms are at play as well, as pRb phosphorylation by cyclin D/CDK4 in differentiated cardiomyocytes isolated from neonatal rat induces their hypertrophic growth but not their proliferation (17). Cyclin-CDK complexes are regulated by two structurally defined classes of inhibitors (CKIs): INK4 and CIP/KIP families.…”
mentioning
confidence: 63%
“…The accumulation of pRb plays a critical role in regulating cell cycle arrest associated with terminal cardiac muscle differentiation, as also observed in other in vitro culture systems, including skeletal muscle, adipocytes, and macrophages, suggesting that this may be a general phenomenon (5,15,16). However, other mechanisms are at play as well, as pRb phosphorylation by cyclin D/CDK4 in differentiated cardiomyocytes isolated from neonatal rat induces their hypertrophic growth but not their proliferation (17). Cyclin-CDK complexes are regulated by two structurally defined classes of inhibitors (CKIs): INK4 and CIP/KIP families.…”
mentioning
confidence: 63%
“…Earlier studies [38][39][40] indicated that the retinoblastoma protein seems to be critical for the ability of cardiomyocytes to undergo cell division. Why this ability in adult life is lost should be the focus of further research studies.…”
Section: Paracrine/endocrine Mechanisms Of Msc Reparative and Regenermentioning
confidence: 99%
“…Recent evidence indicated that cyclin D kinases (CDKs) were up-regulated by hypertrophic stimuli, and CDKsretinoblastoma protein (Rb) pathway may be involved in cardiac hypertrophy [10][11][12]. However, the mechanism underlying activation of CDKs-Rb pathway is not well understood.…”
Section: Introductionmentioning
confidence: 97%